Rapidly Deployed Phone‑Based COVID‑19 Telemedicine Clinic in Lebanon: A Retrospective Analysis - Rabih Soubra; Rim Taleb; Ibrahim Chehab; Yahya Makkieh; Alissar El Sibai; Issam Shaarani (Annals of Global Health, 2026)
Background: In early 2021, Lebanon’s second COVID‑19 wave coincided with financial collapse, health‑workforce emigration, and the aftermath of the August 2020 Beirut port explosion, leaving hospitals saturated and many households unable to afford routine medical advice. Objectives: To describe the design, utilization, disposition outcomes, supervisory escalation, and direct operational cost of a free phone‑based telemedicine clinic rapidly deployed through an academic–nongovernmental organization (NGO) partnership, and to identify transferable lessons for other crisis‑affected, resource‑constrained settings. Methods: Beirut Arab University Healthcare Center and the Federation of Businessmen for Support and Development (IRADA), a national NGO, launched a free 24‑hour, 7‑day‑a‑week phone‑based telemedicine clinic staffed by 40 medical interns and residents using a standardized COVID‑19 management protocol under a two‑tier supervision model, with on‑call family physicians reachable throughout each shift. WhatsApp voice calls were offered to provide free access, and missed calls were returned by the on‑call responder. We retrospectively analyzed the de‑identified records of all consultations managed during 14 weeks (February 2 to May 11, 2021); disposition categories were derived from the free‑text recommendations using a rule‑based classifier. Findings: The service managed 2953 consultations from all Lebanese governorates. After clinical assessment and safety‑netting, 90.1% of consultations were managed outside hospitals at the point of consultation, 7.8% were referred to the emergency department, and 2.0% to primary care. The on‑call family physician was consulted in 6.6% of consultations, concentrated on the highest‑acuity calls (16.5% of emergency department referrals). The overnight window carried 3.7% of consultations but a higher emergency department referral proportion (12.8%). Direct operational cost was USD11,032 (USD3.74 per consultation), excluding non‑monetary university contributions. Conclusions: An academic–NGO partnership, a standardized triage protocol, and tiered supervision can mobilize a trainee workforce safely, at low cost, and within days during a public health emergency.